Peningkatan Produksi Sayuran dan Ikan secara Terpadu dalam Sistem Bioflok-Akuaponik di Kelurahan Tanjung Johor Kota Jambi - Zulkarnain, Zulkarnain; Eliyanti, Eliyanti; Ichwan, Budiyati; Irianto, Irianto; Adriani, Adriani (Universitas Sebelas Maret, 2022)
Increasing Production of Integrated-Vegetable and Fish in the Biofloc-Aquaponic System in Tanjung Johor Village, Jambi City. Tanjung Johor is a fish-producing center in Jambi City. However, the biofloc pond of Sekintang Dayo Farmers Group was minimally managed, so the fish yield and the farmer's income is low. The technology that was the potential to be applied was biofloc-aquaponics. Biofloc-aquaponics technology is a technology in agriculture which is integrated vegetable and fish cultivation. This technology was considered adaptive and effective in Tanjung Johor Village because this area was a populated residential area, limited land availability, prone to flooding, and the community still faced food sufficiency problems. The main principle of this technology was to conserve soil and water and increase farming efficiency through the use of nutrients from fish feed residues as a nutrient source for plants, so it is environmentally friendly. The objective of this community service was to overcome problems in the community, especially members of the Sekintang Dayo farmer group, through simple environmentally friendly technology, namely biofloc-aquaponics in integrated fish and vegetable cultivation. This activity used Participatory Rural Appraisal (PRA) method, where members of the Sekintang Dayo Fish Farmer Group interact with each other to identify the problems they face and find appropriate solutions. Group members actively followed, applied, and developed technology of biofloc-aquaponics cultivation. The program evaluation at the final stage of this activity showed an improvement in farmers' understanding and skills from 49.29% to 97.14%. The farmer group members are admitted to develop the knowledge gained and will design their own biofloc-aquaponic device by utilizing existing resources.